Analyzing the barriers to putting corporate financial expropriations to a halt: A structural modeling of the phenomenon - Fu, Huang; Abbass, Kashif; Qazi, Tehmina Fiaz; Niazi, Abdul Aziz Khan; Achim, Monica Violeta (Frontiers in Environmental Science, 2022)
Dealing with expropriating investors' money is a demanding issue in the corporate sector. This study aims to unveil the barriers to putting expropriations to halt, extract the structure underlying the relationships among barriers and classify them. The study design entails a literature survey, primary data collection, modelling of the issue and analysis. This study used Interpretive Structural Modeling (I.S.M.) and Matriced Impacts Cruise's Multiplication Appliquée a U.N. Classement (M.I.C.M.A.C.) to address this issue. The study uses a non-probability-based purposive sampling technique. The data were collected from a panel of experts consisting of 12 chief financial officers recruited from companies listed on the Pakistan Stock Exchange, Pakistan, from July to September 2022. We find that a 'complicated legal system' is the most critical barrier to putting expropriations to a halt, followed by barriers such as 'flawed hiring' and 'lack of media attention. In addition, the least critical are barriers such as 'loopholes in laws', 'ineffective law enforcement, 'politicized accountability,' and 'lack of international coordination. It is an original valuable study based on real-time data collected from the respondents having hands-on helm of the companies' financial affairs. This is a seminal practical study for policymakers and other stakeholders to understand the barriers to halting corporate scandals and explain expropriations.